Coleridge's theory of poetry - Sodhi, Meena, 1948- (Calcutta : Writers Workshop, 1992)
Study of Samuel Taylor Coleridge, 1772-1834.
Originally presented as the author's thesis (Ph. D.--Banaras Hindu University, 1982).
Includes bibliographical references (p. [170]-178).
Keywords: Coleridge, Samuel Taylor, -- 1772-1834 -- Aesthetics; Poetics -- History -- 19th century